(untitled) (Research, Society and Development, 2021)
Pigeons that share the same space as humans appear to be harmless to health, however, these birds represent a problem for public health, given that they have the ability to spread diseases through their feces, one of which is cryptococcosis, of the species Columba livia. For reasons of having contact with people, to feed themselves can increase the spread of pathogenic agents to humans. In view of this research, this study aims to make a bibliographical survey on some diseases propagated by pigeons and an analysis of the presence of pathogens in the feces of urban pigeons present in the city of Campina Grande - PB, through laboratory investigation, with the purpose of making suggestions and to alert the population about health risks and losses, aiming at the adoption of effective control standards. Four samples of pigeon excreta were collected and sent for laboratory analysis. The collection was carried out in two points that present great infestation of pigeons, all the collection was carried out with the use of disposable and sanitized materials, therefore properly refrigerated to maintain the integrity of the samples. We did not find the presence of pathogenic agents in the investigated sample, however, this amount of sample was quite limited, and future studies are needed with a greater number of excreta of this type of bird.